Stiffness and Strength of Granular Soils Improved by Biological Treatment Bacteria Microbial Cements - Jalili, Mehdi; Ghasemi, Mohmad Reza; Pifloush, Ali Reza (Ital Publication, 2018)
In some parts of the world mechanical properties of problematic soils are not suitable for construction purposes. Today, regard to the importance of the soil improvement; by considering methods with more concordance with the environmental mechanisms in the nature, and with study and combination of geotechnical science, microbiology and geochemistry; researchers try to provide a suitable way to improve the physical and mechanical properties of the problematic soils. In this paper, the effect of the aerobic microorganisms of Sporosarsina Pasteurii (PTCC 1645), as a producer of Urease for the sedimentation of calcium carbonate and improvement of granular soil of Garmsar Industrial Town is evaluated experimentally in order to check the effects of this phenomena on the shear strength and stiffness of the granular soils. The results of the uniaxial compressive strength tests show the effect of adding the above mentioned microbial solution to the soils, in case of increased uniaxial compressive strength and stiffness of the soil. It should be mentioned that the granular soils have no compressive strength, naturally but after bio cementation the samples got notable values.